STRATEGI MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN LCD PROYEKTOR DAN MODEL PEMBELAJARAN BERBASIS MASALAH - Eko Hadi Purnomo; Endang Surjati; Onik Farida Ni'matullah (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to: (1) analyze the effect of the use of LCD projectors and problem-based learning models (PBM) on the learning outcomes of elementary school students, (2) analyze the influence of the use of LCD projectors on student learning outcomes, (3) analyze the influence of problem-based learning models (PBM) on student learning outcomes. This research is quantitative. Data collection techniques include; observations, questionnaires, and documents. The results of the study show that: 1). There is a significant influence between the use of LCD projector (X1) and the problem-based learning model (PBM) (X2), on the learning outcomes of students in grades IV and V in cluster 7, which is 70.005% with a significant value of 0.000. 2). The use of LCD has a positive effect on the learning outcomes of students in grades IV and V in cluster 7, which is 50.71% or can be rounded up to 51%. 3). The problem-based learning model (PBM) has a positive effect on the learning outcomes of grade IV and V students in cluster 7 by 58.87% or if rounded to 59%. The conclusion of the study is that there is a significant influence between the use of LCD projectors (X1) and problem-based learning models (PBM) (X2), on the learning outcomes of students in grades IV and V in cluster 7.